Preprint Abstracts in Times of Crisis: a Comparative Study with the Pre-pandemic Period - Bordignon, Frédérique; Ermakova, Liana; Noël, Marianne (HAL (Le Centre pour la Communication Scientifique Directe), 2021)
International audience